Faculty's perceptions of the liaison program of the Rizal Library of the Ateneo de Manila University - Corpuz, Eduardo Q (2005)
Many academic libraries have increasingly extended their reach through strategic partnerships, collaborative relationships and mutually beneficial alliances and creative ventures to promote their services and successfully carry out and accomplish their missions and goals. The immediacy of access to information makes it very vital to enhance partnerships between faculty and librarian. Success in fostering faculty-librarian collaboration depends on understanding the perceptions of such a relationship.